Giving Reinforcement with 2.0 Framework by Teacher: A Photovoice of Undergraduate Students in the EFL Classroom - Desy Pusparini (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
Abstract - Reinforcement has been used in many areas of educational institution. In the learning activity, reinforcements are given by the teacher as feedback for what students have done. By using reinforcement in the learning activity, the students are expected to feel comfortable to show themselves by responding questions, giving feedback, and expressing their opinions in the class. This study aims to investigate the effect of giving reinforcement by the teacher towards student's learning motivation. This research used the photovoice method and SHOWeD Analysis. The participants are 27 students in 5th semester of English Education Department in online class, consists of 7 males and 20 females with the average age of around 19-21 years old. The finding shows that giving reinforcement encourage student's motivation in the learning activity. As the implication, teachers apply reinforcement in order to make the students high-motivated in the class.